Struktur dan Tingkat Pendapatan Rumah Tangga Petani Karet di Desa Sungai Jalau Kecamatan Kampar Utara Kabupaten Kampar - Maharani, Evy; ', Nurafni; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Rubber plant is one of the plantation crop which has the potential to be developed at Sungai Jalau Village because it is one of the high producers village of rubber plant in the North Kampar. Some differences were found in the income of the Rubber farmer because of different purchasing offered by the employer. The purpose of this study to analysis the structure and level of house income of rubber farmers at Sungai Jalau Village. The method used in this study is a survey method by using purposive sampling. Total populations of 110 rubber farmers were taken which are subscribed by 3 major employers and then 28 farmers were sampled according to the criteria of the study. The results of the study shows that the agricultural sector is the largest contributor to the total household income of rubber farmers is 73,82% and the rest 26,18% was contributed by the revenues of non-agricultural sector. The total average household income received from primary income is Rp.2.098.057/month (63,21%) and additional income is Rp.424.120/month (12,78%), and the total average household income received from other family members is Rp.797.077/month (24,01%), while the average per capita income is Rp.7.966.210/year. Keywords: Structure, household income, household, rubber farmers, per capita income